Meningkatkan Hasil Belajar Matematika Kelas XI Materi Garis Singgung Lingkaran melalui Penggunaan Media Papan Lingkaran - Nur, Sholihin P.; Badu, Syamsu Qamar; Isa, Dewi Rahmawaty (Jambura Journal of Mathematics Education, 2024)
Mathematics is a foundational subject essential for the advancement of technology and various scientific disciplines. This study aims to enhance the mathematics learning outcomes of class XI-C students at SMA Muhammadiyah Batudaa through the use of circle board learning media. Conducted as classroom action research during the 2023/2024 academic year, the study involved 28 students from class XI-C. Data collection methods included tests and observations, utilizing essay tests and observation sheets to assess teacher and student activities. The findings reveal that implementing circle board learning media significantly improved student learning outcomes on circle tangent material. Observations showed notable increases in teacher activity: from 70% to 95% in preliminary activities, 69,4% to 97,2% in core activities, and 68,7% to 93,7% in closing activities. Similarly, student activity observations improved from 75% to 90% in preliminary activities, 67,8% to 92,8% in core activities, and 58,3% to 91,6% in closing activities. These results demonstrate that the use of circle board learning media effectively enhances students' mathematics learning outcomes.